UPAYA MENINGKATKAN PERKEMBANGAN SOSIAL MELALUI BERMAIN BALOK PADA ANAK USIA 5-6 TAHUN - Ade Septiawati; Revina Rizqiyani; K Kisno (Institut Agama Islam Negeri Metro, 2020)
This research begins with the social development of children in the B2 group 5-6 years old at TK Pertiwi Metro Pusat which is still relatively low. This is caused, because the social behavior of students is still lacking such as sharing, cooperation, and help to help, not yet the maximum method used in developing children's social development. Playing with blocks has the advantage to improve children's social honing so that good socialization arises towards other people or their playmates. Classroom Action Research (CAR) consists of planning, implementing, observing, and reflecting. This research was conducted in two cycles and in each cycle consisted of three meetings. Data collection was carried out using observation sheets, structured interviews, and documentation. Data on children's social development in learning activities are obtained from qualitative data through the vision of students' social development during the learning activities process by observation, while quantitative data through observation during the learning process by playing blocks such as observation sheets of teacher and student activities. Based on the results of the study showed that through playing with blocks can improve social development of children in the B2 group aged 5-6 years at TK Pertiwi Metro Pusat in the Academic Year 2018/2019. Keywords: Social Development, Playing Blocks, Early Childhood Education